DEVELOPMENT OF E-MAGAZINE AS LEARNING MEDIA FOR INDONESIAN SALAD TO INCREASE THE KNOWLEDGE OF CULINARY STUDENTS IN INDONESIAN FOOD PROCESSING COURSES - Luthfi Riyadh Rahman; Badraningsih Lastariwati; Fitri Rahmawati (Journal of Research in Social Science and Humanities, 2025)
The culinary arts play a crucial role in preserving and promoting traditional Indonesian cuisine, yet many students lack comprehensive knowledge about the various regional salads. This study aims to develop an e-magazine as an innovative learning media to enhance culinary students' understanding of Indonesian salads in food processing courses. The research employs a design-based approach, involving the creation of an interactive e-magazine that incorporates multimedia elements such as videos, images, and quizzes to engage students effectively. A pilot study was conducted with a sample of culinary students, who evaluated the e-magazine's content, usability, and overall effectiveness as a learning tool. The results indicate a significant improvement in students' knowledge and appreciation of Indonesian salads after utilizing the e-magazine. This research underscores the potential of digital media in culinary education, providing a scalable model for integrating technology into traditional food processing curricula. The findings suggest that e-magazines can enhance learning experiences, foster greater engagement, and improve the retention of culinary knowledge among students